Audit Energi Awal Pada Pompa Distribusi Sampangan dan Pompa Transport Kaligarang Perumda Air Minum Tirta Moedal Kota Semarang - Ghalib Ghibran Wahab; Ervin Nurhayati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Perumda Tirta Moedal Drinking Water Semarang City has seven units of water treatment plants (IPA) with a capacity of 2760 litres/second. To distribute the water produced by Perumda Tirta Moedal Drinking Water, Semarang City uses 145 units of water pumps, which causes high energy costs. Based on the Summary Book of BUMD Performance for the Implementation of Drinking Water Supply System (SPAM) in 2023, the energy cost of Perumda Tirta Moedal Drinking Water Semarang City is IDR 392/m3, where the value of this energy cost is higher than the national average. The high cost of energy, especially electricity, currently makes the company's operational burden even heavier if good energy management and efficiency are not carried out. The first step that can be taken is to carry out an energy audit to assess the efficiency of the pump and determine the Specific Energy Consumption (SEC) value. When carrying out an initial energy audit, data relating to flow, pressure and electrical parameters are collected. The samples in this initial energy audit are the Sample Distribution Pump and the Kaligarang Transport Pump which have a pump efficiency value of 42.96% and the Kaligarang Transport Pump which has a pump efficiency value of 54.95%. Based on the pump efficiency value, Perumda Tirta Moedal Drinking Water needs to take steps to improve energy efficiency.